NUMERICAL INVESTIGATION OF THE CAVITATION IN PUMP INDUCER (Journal of Engineering, 2009)
A numerical investigation of the non-cavitating and cavitating performance of a three-blade pump inducer under nominal and off-design operating conditions is presented. Three different simulated hydrofoils; a flat plate, “NACA0004", and "Clark-Y-6%" has been selected to represent the profile of the inducer blade. A 2D, steady, incompressible, turbulent, and isothermal flow field between the inducer blades is simulated using the FVM. The "Interface Tracking" model is selected to predict the cavity profile of the attached cavitation and the cavitating performance drop. For each blade profile, the influence of solidity in the range of (1.8 to 3.0) and blade angle in the range of (20° to 35°) on the inducer performance is studied. Comparing the present model with available experimental and numerical results, confirms that the developed model well predicts the general non-cavitating performance for an inducer having a flat plate blade profile. For "NACA0004", or "Clark-Y-6%" hydrofoil blade profiles, a reduction in the operating range of these inducers is produced. In addition, the developed model predicts the inception of cavitation earlier than the experimental results. The predicted cavitating head drop curve of an inducer having a flat plate blade profile is compared with available experimental results and a good agreement is obtained. The drop curve occurs suddenly and simultaneously with the experimental one. For "NACA0004“, or "Clark-Y-6%" hydrofoil blade profiles, a smooth curves with simultaneous or gradual head drop occurs with the experimental one, respectively. Generally, the agreement between the results is satisfactory